Публікації "Одеського вісника" як джерело з історії Бердянська останньої чверті ХІХ ст. (Zaporizhzhia Historical Review, 2021)
The author investigates informative potential of “Odessky Visnyk” (“Odessa Herald”) as a source of materials from Berdyansk municipal history in the last quarter of XIXth century. The author comes to the conclusion that publications of the current media are one of the most significant, exhaustive and informative source complex for the history of this seaside town.